Shared Spaces: Decoding Dual Dermatoses in a Single Dermatome - S Dinesh Kumar; J Iswariya; Navya Donaparthi; Debdeep Mitra (Clinical Dermatology Review)
We present the case of a 24-year-old male with a unique concomitant presentation of herpes zoster and alopecia areata within the same dermatome. The patient initially reported painful, clear, fluid-filled vesicular lesions localized to the left side of his abdomen for 1 week. Examination revealed grouped vesicles on an erythematous base limited to the left T10 dermatome. Coincidentally, periumbilical alopecia areata was noted. The patient reported hair loss in the periumbilical region 3 days after the onset of herpes zoster lesions. This case highlights “transitory alopecia areata as a cutaneous complication of varicella zoster infection.” The transient and localized nature of the hair loss suggests a possible effect of the virus on dormant hair follicles within the affected dermatome. This dual manifestation of herpes zoster and alopecia areata is rare, adding to the spectrum of cutaneous complications associated with herpes zoster. Further studies may elucidate the pathophysiology of this concurrent presentation.